The dynamical evolution of molecular clouds near the Galactic Centre: II. Spatial structure and kinematics of simulated clouds - Kruijssen, Diederik; Jeffreson, Sarah; Petkova, Maya A. (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. The evolution of molecular clouds in galactic centres is thought to differ from that in galactic discs due to a significant influence of the external